2003
DOI: 10.1177/030802260306601205
|View full text |Cite
|
Sign up to set email alerts
|

The Journey of a Visually Impaired Student becoming an Occupational Therapist

Abstract: This opinion piece outlines the personal reflections of a visually impaired student's experience throughout her studies, both at university and on placement. Its purpose is to raise awareness of students with disabilities in 2003, the European Year of Disabled People. By highlighting relevant literature and drawing on personal experience, some recommendations are made for the future. Government policy in the United Kingdom aims to remove the barriers to education and to subsequent employment for those with dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Participants in the study identified that in addition to environmental factors and occupational (program) demands, that their personal qualities impacted their sense of fit. Qualities such as persistence, resourcefulness, creativity, optimism, and determination were identified as necessary in this study and are echoed across the literature to describe student occupational therapists with disabilities (Archer, 1999;Sivanesan, 2003;Velde et al, 2005). Therefore when considering inclusive education in occupational therapy it is prudent to consider personal attributes of students with disabilities in addition to environmental and occupational issues.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Participants in the study identified that in addition to environmental factors and occupational (program) demands, that their personal qualities impacted their sense of fit. Qualities such as persistence, resourcefulness, creativity, optimism, and determination were identified as necessary in this study and are echoed across the literature to describe student occupational therapists with disabilities (Archer, 1999;Sivanesan, 2003;Velde et al, 2005). Therefore when considering inclusive education in occupational therapy it is prudent to consider personal attributes of students with disabilities in addition to environmental and occupational issues.…”
Section: Discussionmentioning
confidence: 92%
“…Four themes emerging from this study include the following: students had a desire to "work around [their disability]", (p. 85), they desired support and understanding both within and outside the academic environment, they understood that disability was an essential part of who they were, and they believed that having a disability would enhance their practice. Other published literature relating to student occupational therapists with disabilities consists primarily of individual narratives (Archer, 1999;Murray, 2002;Sivanesan, 2003). In the majority of the literature explored, student occupational therapists with disabilities identified consistently attitudinal, social, physical, and institutional barriers (Bielke & Yssel, 1999;Jung, Salvatori, Tremblay, Baptiste & Sinclair, 2008;Tinklin, et al, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Disabled occupational therapy students describe struggles to get accommodations, and varied experiences with instructor attitudes (22,(24)(25)(26)(27). Fieldwork education and the preparation of preceptors has been a particular challenge; most practice settings lack resources and supports that may be available at universities (22,(24)(25)(26)(27). Students have faced negative attitudes, lack of supports, lack of understanding and awareness, being treated like clients, and internalized anxieties (28).…”
Section: Disability In Occupational Therapymentioning
confidence: 99%